Pemanfaatan Barang Bekas sebagai Alat Peraga Edukasi Ramah Lingkungan Sekolah PAUD di Kota Yogyakarta - Dewi Sekar Kencono; Atik Septi Winarsih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
This paper has the aim of demonstrating the importance of environmentally friendly educational props by utilizing used goods. The implementation of teaching and learning activities at Pre-Kindergarten Kota Yogyakarta has problems with limited educational aids (APE). The existence of APE is one of the keys in carrying out the learning process. The low level of teacher creativity in making APE, in this case, becomes the anchor to provide APE for the learning process. This APE can be made by enhancing the creativity between teachers and parents of parents. During the Covid-19 pandemic, teaching and learning activities in Pre-Kindergarten were carried out in their respective homes. To support the use of APE, training on the use of used goods was conducted. Through training in the use of used goods, the aim is to utilize items around and be used as children's learning media for teachers and parents. In addition, to increase the creativity of teachers and parents. Used goods are recycled into useful items. The use of used goods reduces the increasing waste of waste. Through training on the use of used goods as educational props, it can facilitate learning methods both at home and school for early childhood and reduce waste of used goods.